1995
DOI: 10.1002/j.1552-4604.1995.tb05003.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose and Steady‐State Pharmacokinetics of Fosinopril and Fosinoprilat in Patients with Hepatic Impairment

Abstract: The single-dose and steady-state pharmacokinetics of the angiotensin-converting enzyme (ACE) inhibitor fosinopril and its active diacid, fosinoprilat, were evaluated in 6 healthy volunteers and 12 patients with alcoholic cirrhosis. Fosinopril was administered at a dosage of 10 mg once daily for 14 days. Results in the two groups were similar, with no evidence of accumulation of fosinoprilat in hepatically impaired patients. Mean (+/- SD) maximum observed plasma concentrations of fosinoprilat in the healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…One study demonstrated no differences in mean blood pressure change, even though the AUC of enalaprilat was lower in the cirrhotic group than in the normal subjects, 72 whereas another showed no change in systolic blood pressure, but the decrease in diastolic blood pressure was comparable 73 . Ford et al showed no effect of fosinopril on blood pressure in either alcoholic cirrhotic patients or healthy volunteers, perhaps explained by these patients being normotensive at baseline 84 . Enalaprilat and lisinopril caused comparable decreases in blood pressure in normal subjects and cirrhotic patients; however, the mean baseline blood pressure was higher in the patients 76…”
Section: Effects Of Hepatic Impairmentmentioning
confidence: 98%
“…One study demonstrated no differences in mean blood pressure change, even though the AUC of enalaprilat was lower in the cirrhotic group than in the normal subjects, 72 whereas another showed no change in systolic blood pressure, but the decrease in diastolic blood pressure was comparable 73 . Ford et al showed no effect of fosinopril on blood pressure in either alcoholic cirrhotic patients or healthy volunteers, perhaps explained by these patients being normotensive at baseline 84 . Enalaprilat and lisinopril caused comparable decreases in blood pressure in normal subjects and cirrhotic patients; however, the mean baseline blood pressure was higher in the patients 76…”
Section: Effects Of Hepatic Impairmentmentioning
confidence: 98%
“…Для фозиноприла характерно меньшее количество побочных эффектов по сравнению с другими представителями этого класса лекарственных препаратов, в частности более редкое возникновение кашля, что позволяет рассчитывать на хорошую компла-ентность пациентов к лечению. Двойной компенсаторный путь выведения позволит назначать этот препарат пациен-там с нарушенной функцией почек [9][10][11].…”
Section: результаты и обсуждениеunclassified
“…Отмечается край-не низкая частота возникновения сухого кашля [26]. Имеются доказательства, что сухой кашель, вызываемый другими иАПФ, ослабевает или даже полностью исчезает при переходе на прием фозиноприла [27,28]. Важен факт, что основные параметры фармакокинетики не раз-личаются у пожилых и молодых больных.…”
Section: эффективность иапф в лечении аг с позиции доказательной медиunclassified